Improved Solubility and Dissolution Release Profile of Lurasidone by Solid Self-Nanoemulsifying Drug Delivery System. Issue 2 (3rd March 2016) - Dondapati, Deepthi; Srimathkandala, Madhavi Harika; Sanka, Krishna; Bakshi, Vasudha
Abstract: The purpose of the study was to investigate self-nanoemulsifying drug delivery system (SNEDDS) as potential delivery system for poorly water soluble drug Lurasidone (LUR). SNEDDS was formulated using oil (Anise oil) surfactant (Tween ® 80), and co-surfactant (Polyethyleneglycol-600). Z-average size, PDI and in-vitro drug release were considered to screen and optimize the composition of liquid-SNEDDS. Following emulsification, the optimized formulation was selected to have the smallest mean particle size and highest absolute zeta potential, which would yield stable emulsion. Scanning electron microscopy, X-ray powder diffraction studies confirmed that there was no crystalline drug in Solid-SNEDDS. Fourier transform infrared (FTIR) spectroscopy study revealed that there was no measurable chemical interaction of drug with the carrier. There was no significance difference in zeta average, zeta potential, and release profile of developed formulation before and after stability study. Both Liquid-SNEDDS and solid-SNEDDS showed improved in-vitro drug release than the pure drug. This paper provides an overview of the SNEDDS of LUR as a promising alternative to improve solubility and dissolution release profile. The results suggested that the SNEDDS could be used as an effective oral dosage form to improve the oral delivery of poorly water soluble drug LUR.